POLA KOMUNIKASI GURU DALAM PROSES BELAJAR MENGAJAR DI TPQ ROUDLOTUL QUR’AN SEDAH JENANGAN PONOROGO - Husnaya Amalina Ayyahin; Andhita Risko Faristiana (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2022)
Communication patterns are part of the communication process, where this communication process is a series of activities that convey messages until reciprocity is obtained. Through good communication patterns, it can provide a very positive response to the development of students and the teaching and learning process so as to create an effective communication for communicators and communicants. This study aims to explain: (1) What is the form of teacher communication in the teaching and learning process at TPQ Roudlotul Qur'an with their students. (2) How are the communication patterns of teachers in the teaching and learning process at TPQ Roudlotul Qur'an with their students. The research method used is a qualitative descriptive approach. Data collection techniques used are observation, documentation and interviews. The data analysis used is data reduction, data presentation, and conclusion or verification. The results obtained from this study are 1. Forms of communication patterns carried out by teachers in the teaching and learning process at TPQ Roudlotul Qur'an with their students, namely group communication. However, there are some teachers who occasionally use interpersonal communication to establish closeness with students. 2. The teacher's communication patterns carried out in the teaching and learning process at TPQ Roudlotl Qur'an are one-way, two-way and multi-way communication patterns. But of the three communication patterns, the one-way communication pattern dominates. This is because there are still teachers who are monotonous and do not innovate so that students feel bored and do not provide feedback when the teacher communicates.